Tracking selves or tracking relationships? Means of measuring time amongst Ethiopian runners - Crawley, M. (Journal of the Royal Anthropological Institute, 2021)
GPS watches and digital self-tracking devices (DSTDs) have been characterized as 'self-tracking' devices, assuming a dyadic relationship between individuals and technologies. Amongst Ethiopian professional runners, such devices have become increasingly sought after, and yet they are embedded in deeper relationships of collaborative work, submission, and authority. They circulate between people, tracking relationships as much as they track selves. I place their use in the context of the discourses and practices of two of the main corporations working with runners in Ethiopia to suggest that the logic of exponential acceleration upon which these corporations rely is contested by Ethiopian runners, who attempt to achieve a synthesis between external scientific knowledge and pre-existing ideas about energy, risk, and collective work. Whilst DSTDs may offer a tantalizing opportunity to give in to individualistic urges, in fact they crystallize existing tensions in Amhara society between centrifugal desire and duties of care and reciprocity.